From Warkworth House to the 21st century care homes: progress marked by persistent challenges. (25th July 2022) - Gordon, Adam L; Spilsbury, Karen; Achterberg, Wilco P; Adams, Rich; Jones, Liz; Goodman, Claire
Abstract: Long-term care homes play an essential role within health and social care. Successful measures to support older people at home for longer have led to increased prevalence of disability, frailty and cognitive impairment in those who live in care homes over the last two decades. The need for care home places is projected to increase for the next two decades. Modern care homes provide care for people who are predominantly over 80, have multiple long-term conditions, take multiple medicines, are physically dependent and live with cognitive impairment. Residents do better when services recognise the contributions of staff and care home providers rather than treating residents as individual patients living in a communal setting. There is a strong case given residents' frailty, multimorbidity and disability, that care should be structured around Comprehensive Geriatric Assessment (CGA). Care should be designed to allow opportunities for multiprofessional teams to come together for CGA, particularly if healthcare professionals are based outside care homes. Good data about care homes and residents are central to efforts to deliver high quality care—in some countries, these data are collected but not collated. Collating such data is a priority. Care home staff are under-recognised and underpaid—parity of pay and opportunity with NHS staff is the bare minimum to ensure that the best are recruited and retained in the sector. During the COVID-19 pandemic, residents and relatives have frequently been left out of decisions about policies that affect them, and better consultation is needed to deliver high quality care.